Sociodemographic predictors of mental health problems among adolescents in Indonesia: Evidence from SDQ-based cross-sectional analysis - Dyah Wahyuningsih; Widyo Subagyo (Institute Of Computer Science (IOCS), 2026)
The incidence of mental health problems among adolescents (aged 10-14 years) is increasing, causing a burden of disease. This study aimed to determine the relationship between adolescent characteristics and mental health problems. The study employed a quantitative method with a cross-sectional study design. The sample consisted of 315 junior high school and senior high school students in the Kebasen Subdistrict, Banyumas Regency. Proportionate stratified random sampling was used for sample selection. Data collection was carried out using the Strengths and Difficulties Questionnaire (SDQ), and the data were analyzed using the Chi-Square test. The research findings indicated that age, gender, history of psychological distress, child's education, parental education, school type, and socioeconomic status were significantly associated with mental health difficulties (p-value < 0.05). The variables most significantly contributing to the likelihood of developing mental health difficulties were early adolescence (p-value < 0.05; OR 6.75), low socioeconomic status (p-value < 0.05; OR 6.42), and a history of psychological distress (p-value < 0.05; OR 5.75). Conversely, child's and parental education, as well as school type, showed significant associations but with a lower likelihood. Variables significantly associated with and increasing the likelihood of prosocial mental health problems included a history of psychological distress (p-value < 0.05; OR 11.04), early adolescence (p-value < 0.05; OR 3.78), and low socioeconomic status (p-value < 0.05; OR 2.19). School-based mental health interventions are needed to reduce risk factors and promote adolescent mental health.